All-Arthroscopic McLaughlin's Procedure in Patients with Reverse Hill–Sachs Lesion Caused by Locked Posterior Shoulder Dislocation - Brilakis, Emmanouil; Malahias, Michael-Alexander; Patramani, Maria; Avramidis, Grigoris; Gerogiannis, Dimitrios; Trellopoulos, Angelos; Antonogiannakis, Emmanouil (Joints, 2019)
Purpose This study aims to investigate the clinical and functional outcomes of the all-arthroscopic McLaughlin procedure in a clinical series of patients suffering by neglected locked posterior shoulder dislocation.Methods A retrospective clinical study based on prospectively collected data was conducted in a single center regarding 10 patients with neglected locked posterior shoulder dislocation and concomitant reverse Hill–Sachs lesion, who were treated with the all-arthroscopic Mclaughlin procedure. The average humeral bone defect was 39 ± 7% according to the preoperative computed tomography evaluation. The mean time of follow-up was 77 ± 16 months (range, 63–104 months).Results No patient had suffered a new dislocation, whereas all of them were satisfied with the surgical outcome and returned to their previous activities of daily living. External rotation was restored to every patient studied from 0 degrees at the baseline. At the last follow-up, the median external rotation beside the body was 90 degrees (range, 50–90 degrees; p < 0.01) and the respective measurement at 90 degrees of abduction was 90 degrees (range, 80–90 degrees; p < 0.01). The active forward flexion was increased (p < 0.01), from 60 degrees (range, 30–180 degrees) at the baseline to 180 degrees (range, 160–180 degrees) at the last follow-up and the internal rotation was gained (p < 0.01) from the level of buttock (range, lateral thigh–T12) at the baseline to the T11 level (range, T7–L3) at the last follow-up. The median UCLA score was increased from 8 (range, 4–22) to 35 (range, 33–35; p < 0.01) and the Oxford instability score from 5 (range, 3–16) to 46 (range, 43–48; p < 0.01), respectively.Conclusion The arthroscopic McLaughlin procedure in substantial reverse Hills–Sachs lesion caused by locked posterior dislocation leads to excellent clinical and functional results in the long-term follow-up.Level of Evidence This is a therapeutic study, case series with no comparison group, Level IV.
Keywords: McLaughlin's procedure; reverse Hill–Sachs lesion; posterior shoulder dislocation; arthroscopy